Analysis of the Influence of Competence and Motivation on Employee Performance through Work Discipline as an Intervening Variable - Resi Zelfi Evany; Djatmiko Noviantoro; Sari Sakarina (Cahaya Abadi Publisher, 2026)
This study aims to analyze the influence of competence and work motivation on employee performance with work discipline as an intervening variable. The study used a quantitative approach with a survey method by distributing questionnaires to employees. The study population was all 135 employees with a census sampling technique. Data were analyzed using path analysis to determine the direct and indirect effects between research variables. The variables studied included competence, work motivation, work discipline, and employee performance. The results showed that competence and work motivation had a significant effect on work discipline. Work motivation and work discipline were also proven to have a significant effect on employee performance, while competence had a relatively weak effect on performance. In addition, work discipline was proven to be able to mediate the influence of competence and work motivation on employee performance. The findings of this study indicate that increasing competence and work motivation will be more effective in improving employee performance if supported by a good level of work discipline. This study provides an empirical contribution to the development of human resource management studies, particularly regarding the role of work discipline as an intervening variable in the relationship between competence, work motivation, and employee performance.